Compliance to enhanced recovery program in liver resection surgery: A retrospective cohort study - Abiya Pradhan; Anshuman Sarkar; Srimanta Haldar; Arunangshu Chakraborty; Angshuman Rudra Pal (Journal of Anaesthesiology Clinical Pharmacology)
Background and Aims: Liver resection is a complex surgery, and optimizing recovery is critical to ensure that patients can promptly regain their health and quality of life. The authors present a retrospective cohort study on Enhanced Recovery After Surgery (ERAS) in liver resection aimed at correlating compliance with ERAS elements to length of stay (LOS) and the incidence of complications in a tertiary-level cancer hospital in Eastern India. Material and Methods: In total, 44 hepatectomy patients were assessed retrospectively from June 2022 to May 2023. Data were collected from electronic medical records and patient charts. Results: The overall compliance was 77.7%. Individual component compliance varied. Lower compliance rates were seen with some aspects such as fasting and carbohydrate loading, minimally invasive surgical techniques used, and avoidance or early removal of the drain. The cohort was divided into two groups. Group 1 had compliance to ≥75% of 21 elements of ERAS, and group 2 had compliance to <75%. Statistical analysis showed higher ERAS compliance and reduced complications, although LOS differences were not statistically significant (group 1 and group 2 with an LOS difference of 1 day). Severe complications such as re-exploration and death were noted in the group of patients with compliance to less than 75% of the components. Conclusion: With increased ERAS compliance, the patients benefited clinically and financially.